Light-quark and gluon jet discrimination in [Formula: see text] collisions at [Formula: see text] with the ATLAS detector - Aad, G; Abbott, B; Abdallah, J; Abdel Khalek, S; Abdinov, O; Aben, R; Abi, B; Abolins, M; AbouZeid, O S; Abramowicz, H; Abreu, H; Abreu, R; et al. (The European physical journal. C, Particles and fields, 2014)
A likelihood-based discriminant for the identification of quark- and gluon-initiated jets is built and validated using 4.7 fb[Formula: see text] of proton-proton collision data at [Formula: see text] [Formula: see text] collected with the ATLAS detector at the LHC. Data samples with enriched quark or gluon content are used in the construction and validation of templates of jet properties that are the input to the likelihood-based discriminant. The discriminating power of the jet tagger is established in both data and Monte Carlo samples within a systematic uncertainty of [Formula: see text] 10-20 %. In data, light-quark jets can be tagged with an efficiency of [Formula: see text] while achieving a gluon-jet mis-tag rate of [Formula: see text] in a [Formula: see text] range between [Formula: see text] and [Formula: see text] for jets in the acceptance of the tracker. The rejection of gluon-jets found in the data is significantly below what is attainable using a Pythia 6 Monte Carlo simulation, where gluon-jet mis-tag rates of 10 % can be reached for a 50 % selection efficiency of light-quark jets using the same jet properties.